PERBANDINGAN EFEKTIVITAS PENYELESAIAN SENGKETA KONSUMEN PADA PENGADILAN NEGERI DAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK): Sahlevi Dwinanda - admin, admin (Fakultas Hukum Universitas Islam Jakarta, 2017)
Development and development of the economy in general and specifically in the field of industry and national trade have produced various variations of goods and or services that can be consumed. The presence of the UUPK is a milestone in the development of consumer protection law. One thing that cannot be ruled out is that many consumers are less concerned about their rights, the UUPK states that resolving disputes can be taken through court or outside the court. The research method is normative juridical, and the purpose of this research is to analyzes Law No. 8 of 1999 concerning Consumer Protection, Decree of the Minister of Industry and Trade of the Republic of Indonesia Number 350 / MPP / Kep / 12/2001 concerning the implementation of BPSK duties and authorities, and literature on consumer protection. Consumer dispute settlement through the court is only regulated by one of article 48 of the Consumer Protection Law which states that the settlement of consumer disputes through the courts refers to the provisions of the general court that apply with due observance of Article 45. BPSK is formed in the level II area, this is regulated in Article 49 UUPK, as the implementing regulation of the provisions issued Presidential Decree No. 90 of 2001 dated July 21, 2001 concerning the establishment of the Consumer Dispute Settlement Body. As a realization of the presidential decree, BPSK was formed to resolve disputes outside the court. Comparison of the effectiveness of the consumer dispute settlement mechanism at BPSK with the District Court in terms of time, process, and costs in dispute settlement is more affordable if through BPSK first.